Effect of perfluorooctanesulfonate exposure on steroid hormone levels and steroidogenic enzyme activities in juvenile Silurana tropicalis. Issue 7 (7th March 2019) - Fort, Douglas J.; Mathis, Michael B.; Fort, Chelsea E.; Fort, Hayley M.; Fort, Troy D.; Guiney, Patrick D.; Weeks, John A.
Abstract: The impact of the perfluoro‐chemical, perfluorooctanesulfonate (PFOS), on gonadal steroidogenesis during sexual differentiation in Silurana tropicalis was examined because of its ubiquity in the environment, bioaccumulative nature and potential to disturb endocrine activity. A partial life cycle study exposing S. tropicalis to varying concentrations of PFOS 0.06, 0.13, 0.25, 0.50 and 1.0 mg PFOS/L [nominal]) was conducted. Gonad and plasma samples were collected from juvenile control specimens and organisms exposed to PFOS from early embryo through 150 days post‐metamorphosis. Gonad CYP17, aromatase and 5α‐reductase activities were measured. Plasma estradiol, testosterone, dihydrotestosterone (DHT) and gonadal testosterone were measured in both males and females. Increased plasma DHT and gonadal testosterone were found in PFOS‐treated juvenile male S. tropicalis compared to controls. Decreased plasma estradiol, but not testosterone, was detected in PFOS‐treated female S. tropicalis compared to controls. Plasma DHT was not detected and an increase in gonadal testosterone was detected in PFOS‐treated female frogs. Female S. tropicalis exposed to PFOS exhibited a concentration‐related decrease in the mean aromatase activity, but not 5α‐reductase. PFOS exposure in male frogs induced a concentration‐related increase in 5α‐reductase activity, but did not alter aromatase activity compared to control frogs. A concentration‐related increase in CYP 17, 20‐lyase activity, but not 17‐hydroxylase activity, was found in both female and male S. tropicalis exposed to PFOS. Abstract : The impact of the perfluoro‐chemical, perfluorooctanesulfonate (PFOS), on gonadal steroidogenesis during sexual differentiation in Silurana tropicalis was examined because of its ubiquity in the environment, bioaccumulative nature and potential to disturb endocrine activity. A partial life cycle study exposing S. tropicalis to varying concentrations of PFOS 0.06, 0.13, 0.25, 0.50 and 1.0 mg PFOS/L [nominal]) was conducted.